Hemp seed oil ameliorates ulcerative colitis in connection with tryptophan metabolism driven by gut microbiota - Jing Yang; Yiyun Guan; Junjie Zhou; Yujie Zhang; Lixi Li; Hailong Lu; Zhongjie Zou; Mengjuan Gong (Journal of Functional Foods, 2025)
Ulcerative colitis (UC), a chronic inflammatory bowel disease, currently lacks effective therapeutic strategies. This study investigated the protective effects of hemp seed oil (HSO), a dietary supplement derived from hemp seeds (Cannabis sativa L.) possessing anti-inflammatory properties, against UC. Using 16S rRNA sequencing, fecal microbiota transplantation (FMT), and targeted tryptophan (Trp) metabolomics, we explored the mechanisms underlying HSO's effects in dextran sulfate sodium (DSS)-induced UC mice. Results showed HSO significantly alleviated UC symptoms, restored gut microbiota dysbiosis, and increased short-chain fatty acids (SCFAs) production. FMT results revealed HSO selectively promoted Muribaculum and Roseburia growth, enhancing Trp metabolites such as indole-3-acetic acid (IAA) and 3-indolealdehyde (3-IAld). Additionally, HSO upregulated aryl hydrocarbon receptor (AhR) expression and interleukin (IL)-22 production, promoting tight junction protein expression and intestinal barrier repair. These findings suggested HSO as a promising dietary intervention for UC management by targeting gut microbiota-mediated Trp metabolism and the AhR/IL-22 axis.